PERAN AKTIF ORANGTUA TERHADAP EKSPRESI TULIS ANAK - Kumara, Amitya (Jurnal Psikologi, 2000)
This research was aimed to understand parental role in fifth grade students writing ability. Parent’s devotedly attached of literer was obtain to reveal parent’s attention to the development of their children’s writing ability. Children’s writing ability was obtained through writing tasks on the basis of two kinds of stimuli, serial pictures and audiotaped unfinished story. The subject were 189 fifth grade students of SD Ungaran I, SD Ungaran II, SD Bantul I, SD Cepit I dan SD Cepit IV and SD Karanggondang. The students were given the tasks of writing of both stimuli and the scale to obtain their parent’s devotedly attached of literer. The data was correlated by the means of Pearson’s product-moment, the result shows significant correlation between parental involvement and the quality of children’s writing. Higher correlations appear particulary on the aspects of parental care of leissure times, study times, and the aspect of parents’s provision for literacy facilities, in both groups. Keywords: writing ability